QUASISYNTHETIC PHOTOMETRY - Tsymbal, V. (Одеські астрономічні публікації, 2008)
The brief description of new ideas for the flux calibration of stellar spectra are presented. Described approach lets us to produce a lot of reference stars both for ground and space observations. The metodology also opens possibilities to determine the angular diameters from high resolution stellar spectra and analyze the interstellar medium in the direction of a star.